PENGEMBANGAN MINUMAN FORMULA IBU HAMIL DAN MENETEKI BERBASIS BAHAN LOKAL NON SUSU - Almasyhuri Almasyhuri; Nelis Imanningsih; Suryana Purawisastra; Erwin Affandi; Nunung Nurjanah (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
The Development of Non-Milk Based Formulated Drinks For Pregnant and Breastfeeding Women.Background: The pregnant and breastfeeding women need a greater nutrition intake compared to normal women. At second and third trimester of pregnancy, and during breastfeeding, a woman should have additional nutrient for approximately 300 Kcal energy and 17 grams protein per day. Recently, various formula drinks for pregnant and breastfeeding women are available in the market, however most of these formulas are expensive.Objectives: To develop non-milk based formula drinks for pregnant and breastfeeding women which contained adequate amount of additional macro and micro nutrients had good sensory quality and had long self life.Methods: Initially, 13 kinds of drinks were formulated. The drinks contained aproximately 300 Kcal energy and 17grams protein. They were analyzed for nutrient contain, microbiology and sensory quality in order to vote the best 5 formulas at the laboratory scale. The formulated drinks were packaged and sealed in 150 mL plastic cups. To know the self life of the drinks, storage was carry out in the room, incubator and refrigerator temperature during 12 months.Results: From sensory test, it was concluded that the best five drinks were kweni formula, chocholate formula, ginger formula, guava-orange formula and red bean formula. One cup of 150 ml formulated drink, had 140-150 Kcal energy and 8 grams protein. Therefore, to fulfill additional requirements for pregnant and breastfeeding women, the drinks should be consumed 2 cups a day.Conclusions: The formula drink developed could provide additional energy, protein, vitamin and mineral needed by pregnant and breast feeding women. There was no side effect reported by the panelist because of consuming the formula.Keywords: formulated drinks, pregnant women, breastfeeding women, acceptance.